Good Governance in Crisis or a Good Crisis for Governance? A Comparison of the EU and the US - Waltraud Schelkle (London School of Economics and Political Science (LSE), European Institute, 2010)
The crisis since August 2007 provides an opportunity to observe the workings of good governance institutions under an extreme stress test and in radically different political settings. Institutions such as independent central banks, fiscal rules and regulatory oversight of public finances were meant to depoliticize macroeconomic stabilization. The comparison of responses to the crisis in the United States and in the European Union shows that good governance institutions are in crisis in the US while it has been a good crisis for governance so far in the EU. Levels of fiscal stimulus and monetary easing are surprisingly similar between the EU and the US, yet the ECB has maintained its independence and member states have been restrained from inserting protectionist elements in their stimulus measures. By contrast, the boundaries between economic stabilization and distributive politics have been wiped out in the US because neither the political forces in the states nor the economic forces in the financial sector erected many defences. In the EU, the boundaries as drawn are inimical to joint stabilization efforts but this is exactly why they are politically self-enforcing.
Keywords: 330; central bank independence; crisis; depoliticization; European Union; fiscal rules; United States